1997
DOI: 10.1097/00004647-199710000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow during and after 2 Hours of Middle Cerebral Artery Occlusion in the Rat

Abstract: In this study we explored if the secondary bioenergetic failure, which occurs a few hours after recirculation, following transient middle cerebral artery occlusion (MCAO) in rats, is caused by a compromised reflow. We induced 2 hours of MCAO and measured CBF at the end of the ischemia, as well as 15 minutes, 1, 2, and 4 hours after the start of recirculation, using autoradiographic or tissue sampling 14C-iodoantipyrine techniques. After 2 hours of MCAO, the autoradiographically measured CBF in the ischemic cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 49 publications
5
29
1
1
Order By: Relevance
“…5, 6). This reactive hyperemia on reperfusion has been described previously in rat transient MCAO (29,30). At 24 hr, CBF, CBV, and MTT were similar in the ischemic and nonischemic hemispheres (Fig.…”
Section: Il-1 Leads To a Reduction In Cbf On Reperfusionsupporting
confidence: 83%
“…5, 6). This reactive hyperemia on reperfusion has been described previously in rat transient MCAO (29,30). At 24 hr, CBF, CBV, and MTT were similar in the ischemic and nonischemic hemispheres (Fig.…”
Section: Il-1 Leads To a Reduction In Cbf On Reperfusionsupporting
confidence: 83%
“…However, estradiol did not prevent cell death in the striatum region. It was reported that the regionspecific effect partially reflects differential blood perfusion to the cortex and striatum following MCAO: MCAO blocks blood flow to a greater extent in the striatum compared with the cortex [17]. Our results also showed that estradiol markedly decreased the number of apoptotic cells in the cerebral cortex using TUNEL method.…”
supporting
confidence: 71%
“…Also, reperfusion might induce increases in blood flow above basal levels, as it has been reported in animals (Tamura et al, 1980;Traupe et al, 1982;Gourley and Heistad, 1984;Todd et al, 1986;Tsuchidate et al, 1997) and in humans (Kidwell et al, 2001).…”
Section: Introductionmentioning
confidence: 86%